Can cash transfer interventions increase contraceptive use and reduce adolescent birth and pregnancy in low and middle income countries? A systematic review and meta-analysis. - Dylan Kneale; Abel Kjaersgaard; Malica de Melo; Joelma Joaquim Picardo; Sally Griffin; Rebecca S French; Helen E D Burchett (PLOS Global Public Health, 2023)
Becoming pregnant and giving birth under the age of 20 is associated with a range of adverse social, socioeconomic and health outcomes for adolescent girls and their children in Low and middle income countries. Cash transfers are an example of a structural intervention that can change the local social and economic environment, and have been linked with positive health and social outcomes across several domains. As part of a wider review of structural adolescent contraception interventions, we conducted a systematic review on the impact of cash transfers on adolescent contraception and fertility. Fifteen studies were included in the review with eleven studies providing evidence for meta-analyses on contraception use, pregnancy and childbearing. The evidence suggests that cash transfer interventions are generally ineffective in raising levels of contraceptive use. However, cash transfer interventions did reduce levels of early pregnancy (OR 0.90, 95% CI 0.81 to 1.00). There was suggestive evidence that conditional, but not unconditional, cash transfers reduce levels of early childbearing. Given that much of the evidence is drawn from interventions providing cash transfers conditional on school attendance, supporting school attendance may enable adolescent girls and young women to make life choices that do not involve early pregnancy.